Online media scans: Applying systematic review techniques to assess statewide human papillomavirus vaccination activities - Emily Ann Groene; Inari Mohammed; Keith Horvath; Nicole E. Basta; Nicholas Yared; Shalini Kulasingam (Journal of Public Health Research, 2019)
Background. Although the human papillomavirus (HPV) vaccine has been approved for use in adolescents in the US for over a decade, vaccination uptake remains low. Of concern, HPV vaccine coverage is below the national average in Minnesota, USA. To understand the reach of current HPV programming and research, we use an online media scan; this method may be applied to other jurisdictions to gain insight about various public health issues. Design and Methods. This online media scan describes the nature and scope of ongoing activities to increase HPV vaccination in Minnesota. The media scan included: a) structured internet searches of HPV vaccine health education/promotion activities ongoing in Minnesota since 2013, and b) searches in research databases of the published literature on HPV vaccination in Minnesota from 2013 to 2018. Results. Searches resulted in 880 online and 142 research article matches, with 40 and 36 meeting selection criteria. Results were categorized by activities focusing on race/ethnicity, sex, health providers, parents, lesbian, gay, bisexual, transgender and queer or questioning (LGBTQ) populations, geographic location, catchup vaccination, and insurance status. Most activities were statewide (52% health education/promotion and 35% research), followed by activities located in entirely urban areas (15% health education/promotion and 41% research) with only 6% of health education/promotion activities and 2% of research activities carried out in entirely rural areas. Conclusions. A range of local and statewide HPV vaccine health education/promotion and research activities were identified in Minnesota. Several efforts partnered with American Indian and Somali/Somali-American communities, but fewer activities focused on HPV vaccination among LGBTQ youth and HPV vaccination in rural areas.